Two‐year extractability of novel left ventricular, active fixation leads in the sheep model. Issue 11 (14th October 2017) - Adler, Stuart; Kirchhof, Nicole; Thompson, Amy E.; Foerster, Laurie; Marquard, Kyle R.; Hine, Douglas S.
Abstract: Background: A cardiac lead with a side helix for active fixation to the coronary vein wall (Attain Stability ®, Model 20066, Medtronic, Minneapolis, MN, USA) recently received CE Mark. The lead is designed to improve left ventricular (LV) placement and reduce dislodgement rates. The extractability of this active fixation LV lead has not been studied extensively. Methods: Seventeen sheep were implanted with either an LV lead with a side helix (Model 20066, Model 20096, Medtronic) or a unipolar LV lead (Model 4193, Medtronic) as a control. Leads were extracted at approximately 26, 52, or 118 weeks. Standard extraction methodology was employed with quantitative traction up to 907 g (2 lbs.) using a locking stylet. Gross pathology and histology of the heart with particular attention to the lead tracts were performed. Results: All leads were successfully removed in their entirety and required significantly less than 1 kg of traction force. The side helix disengaged from the vein as designed and resulted in no complications. No cardiac tissue was observed on any extracted lead. Gross pathology and histology were devoid of any helix‐induced lesions in the vascular structures. The epicardium over the side helix was normal and the fibrotic reaction around the helix was not significantly different from that around the nonhelix portions of the study leads or the control lead. Conclusion: Extraction of the side helix, active fixation LV lead from the coronary veins in the sheep model is safe, without procedural complexity, and free of complications after long‐term LV lead implant duration.